FURTHER IMPROVEMENT OF METHODS FOR DETERMINING ENERGY EFFICIENCY OF BUILDINGS AND STRUCTURES IN THE REPUBLIC OF KAZAKHSTAN - Sharipov, Rashid; Kudrevich, Olga; Yerzhanov, Syrymgali; Shavdinova, Madina; Tyulyubayeva, Dinara (Journal of Applied Engineering Science, 2020)
One of the most important strategic objectives is to create a sustainable model for the development of the Kazakhstan economy, which is closely linked to the solution of energy saving and energy efficiency in the construction industry. The main principles of the energy efficiency strategy include integrated approach (efficient use of energy at all stages of the facility's life cycle for all types of energy resources, with legal support and organizational and technical control by the state) and systematic approach (the study of the process using general rather than partial approach). The article analyzes key problems and barriers that prevent the successful implementation of energy saving and energy efficiency policies. A significant role in the rational use of energy resources belongs to the regulatory framework. It was revealed that currently existing regulatory and technical documents in the country, unlike similar documents in EU countries, have a number of inaccuracies and disadvantages that do not allow for a full accounting of energy consumption. At present, there is practically no effective methodology for determining the energy efficiency of residential buildings and structures in Kazakhstan. In this regard, a methodology for determining the energy efficiency of buildings and structures, harmonized with EU requirements (taking into account energy consumption for heating, ventilation, high-temperature water supply, cooling and lighting) is currently being developed. The energy efficiency improvement of new, renovated and operated buildings will make it possible to reduce greenhouse gas emissions, thus contributing to solving both global environmental problems and energy and environmental security in the Republic of Kazakhstan.
Keywords: energy efficiency class, certification of energy efficiency performance, energy saving, energy consumption, energy audit, energy-efficient buildings